Tepisari Village Government Strategies in Increasing Communitiy Participation in Development Programs - Putri Larasati Kiyato; Danang Purwanto; Atik Catur Budiati (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
As the development of villages becomes more complex, community participation is considered an important factor for the success of rural development programs. However, the lack of community participation is an obstacle in village development. A strategy from the village government is needed to increase community participation in development. This study aims to determine the Tepisari Village government's strategy in increasing community participation in development programs. The research method used in this research uses a qualitative approach with a case study in Tepisari Village. The data analysis technique in this research uses three stages data reduction, data presentation, and conclusion drawing. This research was analyzed using Geoff Mulgan's theory of government strategy. The results obtained from this study indicate that the Tepisari Village government's strategy in increasing community participation in village development programs has been running as planned. Some of the strategies used include openness, closeness between the village government and the community, improving human resources, and involving community aspirations in planning, implementing, and evaluating the village development process. However, there are several obstacles, namely related to the budget and the limited participation of people who work overseas.